Antara Jilbab dan Niqab Perspekstif Muhammad Nāiruddin al-Albāniy - Abd Majid Abror (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
For al-Albaniy, the discussion about Muslim headscarves is very important because many women who are Muslim women have been deceived by European civilization. While the niqab (niqab), al-Albaniy emphasized that the veil is not obligatory but sunnah and mustahab, he also gives objections to those who require the veil. and also Al-Albaniy in discussing the issue of Muslim headscarves being more thorough, especially when presenting the hadith on the arguments surrounding this hijab. Almost all the hadiths that are used as arguments in this matter, al-Albaniy always performs takhrij and sometimes provides comments (ta'liq) about the sanad of his hadith. As well as stating the requirements for clothing (read: hijab) for Muslim women referred to in the Qur'an and Sunnah he mentions exist.